Memory and history teaching: the interfaces between the training and knowledge of teachers (Tempo e Argumento, 2013)
This article points to reflections on the experiences of teachers of history, and interpret the formation process, its implications and tensions to teacher, from the symbolic elements, choices, do the trajectories of teachers.
Keywords: memory teachers; memory; teaching of history; teacher training